Stability and dynamics in an overlapping generations economy with flexible wage negotiations - Erkki Koskela; Mikko Puhakka (Institute for the Study of Labor (IZA), 2007)
We analyze the stability and dynamics of an overlapping generations model with imperfectly competitive labour markets. By focusing on the right-to-manage wage bargaining we assume that wage is negotiated after the capital stock decision. With Cobb-Douglas utility and production functions the steady state is unique and the steady state capital stock depends positively both on the trade union's bargaining power and on the wage elasticity of labour demand. That elasticity depends either on lower decreasing returns to scale and/or more intensive product market competition. Finally, we show that the steady state equilibrium is a saddle.
Keywords: J51; 330; Overlapping generations economy; capital accumulation; flexible wage negotiation; stability and dynamics; Steady-State-Wachstum; Overlapping Generations; Gleichgewichtsstabilität; Lohnverhandlungen; Investition; Gewerkschaftlicher Organisationsgrad; Theorie